2010
DOI: 10.1021/ma902537e
|View full text |Cite
|
Sign up to set email alerts
|

Retention Behavior of Linear, Branched, and Hyperbranched Polyesters in Interaction Liquid Chromatography

Abstract: The retention behavior of aromatic polyesters possessing different degrees of branching was studied in gradient liquid adsorption chromatography (gradient chromatography), liquid adsorption chromatography (LAC), and liquid chromatography at the critical conditions (LCCC). The chromatographic experiments revealed that retention of linear and branched polyesters is influenced by the degree of branching as well as the molar mass of the polymer samples in all enthalpy-dominated chromatographic modes such as LAC, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Lederer et al used SEC to fractionate linear and hyperbranched polyesters separately and further injected different fractions into SEC‐RI‐MALLS system to obtain the accurate molar mass of linear and hyperbranched samples. They found that the molar mass of the hyperbranched polyesters at the same retention volume was higher than that of linear samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lederer et al used SEC to fractionate linear and hyperbranched polyesters separately and further injected different fractions into SEC‐RI‐MALLS system to obtain the accurate molar mass of linear and hyperbranched samples. They found that the molar mass of the hyperbranched polyesters at the same retention volume was higher than that of linear samples.…”
Section: Resultsmentioning
confidence: 99%
“…[11] Moreover, the f/f 0 of hyperbranched sample is smaller than that of linear polystyrene, indicating the more symmetric structure of hyperbranched samples. [46] Lederer et al [47] used SEC to fractionate linear and hyperbranched polyesters separately and further injected different fractions into SEC-RI-MALLS system to obtain the accurate molar mass of linear and hyperbranched samples. They found that the molar mass of the hyperbranched polyesters at the same retention volume was higher than that of linear samples.…”
Section: Resultsmentioning
confidence: 99%
“…Progresses in separation of polymers are of the highest importance to deal with the complexity of the new materials. Research in new separation methods such as field flow fractionation [45] or liquid adsorption chromatography [46] is gaining momentum. SEC has however more to offer than currently exploited.…”
Section: Discussionmentioning
confidence: 99%
“…The potential applicability of gradient elution chromatography for polyester resins has been documented. [45][46][47][48][49][50] In most cases, reversed phase systems were used although the possibility of normal phase gradient HPLC has also been published. [51,52] The results of samples s23, s25 and s28 in Figure 6 are representative of the different stages of the polyesterification reaction thus the evolution of different species can clearly be followed.…”
Section: Maldi-tof Ms Of Pg/pa and Pg/ma Model Batchesmentioning
confidence: 99%